2021
DOI: 10.25000/acem.929684
|View full text |Cite
|
Sign up to set email alerts
|

Canlı Vericili Karaciğer Naklinde Retrospektif Donör Hepatektomi Sonuçları- Tek Merkez Deneyimi

Abstract: Objectives: We aimed to describe our technique and donor selection for donor hepatectomy, review our case series and report our complication rates and outcomes. Materials and Methods: We retrospectively reviewed 41 consecutive donor hepatectomy cases between October 2019 and November 2020 at Yeditepe University, Istanbul, Turkey. Complications were graded according to Clavien-Dindo classification. All cases were performed via laparotomy. Results: Out of 41 donor cases, 38 (92.6%) were right lobe, 2 (4.8%) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Minimizing the rates of complications related to surgery and ensuring post-operative quality of life in people undergoing donor hepatectomy are crucial for the safety and social incentive dimension of this surgery [ 1 , 2 ]. Therefore, thorough donor preparation is vital to reduce complications.…”
Section: Highlight Key Pointsmentioning
confidence: 99%
“…Minimizing the rates of complications related to surgery and ensuring post-operative quality of life in people undergoing donor hepatectomy are crucial for the safety and social incentive dimension of this surgery [ 1 , 2 ]. Therefore, thorough donor preparation is vital to reduce complications.…”
Section: Highlight Key Pointsmentioning
confidence: 99%
“…Initial studies reported living liver donor complications of up to 50%, but over the decades, living liver donor complications have been reported at around 10-15% [9]. Biliary complications are considered the most common morbidity experienced by living liver donors and can occur in up to 9% of living liver donors [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%